Pengaruh Customer Relationship Management dan Service Quality terhadap Customer Loyalty pada Toko Permata Silver Kersana - Sri Utami Pebrianingsih; Alfred Heriman Setio; Sigit Pamungkas (LPPM UBSI Kampus Kota Tegal, 2025)
The effect of Customer Relationship Management (CRM) and Service Quality (SQ) on Customer Loyalty (CL) at the